Influence of temperature on the distribution of oil products from Pyrolyzing palm oil waste / Mohd Suhaifizan Arifin - Arifin, Mohd Suhaifizan (Faculty of Applied Sciences, 2008)
One of disposal technologies method known as pyrolysis was discovered as a new technologies to dispose solid waste with valuable yield as its main product which are pyrolytic oil and char. Almost same to incineration method which is the most popular solid waste disposal technologies method, the only different between them is pyrolysis consumed no oxygen or too little compare to incineration which need the enough oxygen to incinerate all the waste. Based on this study, the sample of biomass which was oil palm empty fruit bunch has been used to characterize the raw and char produced sample by proximate and ultimate analysis. Yet, the pyrolytic oil produced also has been analyzed to identify the chemical compound presence in the sample by using GCMS. Actually, there are many factors which affect the distribution of oil and the char in pyrolysis process such as temperature of fixed bed reactor, the solid residence time, particle size of biomass sample and the gas flow rate utilized. In this project which was only to investigate the effect of fixed bed temperature in pyrolysis process was proved that the fixed bed temperature playing an important roles in distribution of product yield when the product produced were different in percentage when different temperature had been used. COPYRIGHT ©